A inclusão da comunidade Santa Clara na sociedade da informação - Farias, Maria Giovanna Guedes (2011)
Information science plays a fundamental role in the information society, to devise ways for social inclusion through digital inclusion. Accordingly, we developed this research for the Masters Program in Information Science at the Federal University of Paraíba, to intervene in the process of informational exclusion experienced by the Community of Santa Clara (CSC) in João Pessoa, Paraíba. The intervention happened through field research for registration, organization and dissemination of "information sources" (study subjects) comprised of people of the Community. An action of information has been implemented into the CSC to create the virtual interface "Blog da Comunidade Santa Clara" in the Wordpress platform, to disseminate the wealth of knowledge of those depositors of social memory and knowledge of Santa Clara, which will be available for future generations. The appropriation of the research results (the Blog) by the community generated the extension project "Blog Management Course", within the PPGCI/UFPB, whose purpose was to develop information skills for residents of the Community volunteers to continue the blog. Thus, the result of the research at Santa Clara was increased, in reciprocal action of the Community and as assumption of the action-researchmethodology, the determination to continue the publication of the blog (a virtual interface for communication of information). In addition to the extension project for training of volunteers of CSC, the treasure of knowledge disseminators of the Community, we developed a learning activity through a tutorial for creating blogs, in partnership with the "Laboratory of intellectual Technologies" (Laboratório de Tecnologias Intelectuais - LTi) Department of Information Science, UFPB. The inclusion of CSC's treasure of knowledge in cyberspace, as well as empowerment of the community in intellectual competence to use digital technology of communication of information, can promote the recovery of cultural identity of residents of the CSC and citizenship.